2022
DOI: 10.1371/journal.ppat.1010223
|View full text |Cite
|
Sign up to set email alerts
|

Expansion microscopy of Plasmodium gametocytes reveals the molecular architecture of a bipartite microtubule organisation centre coordinating mitosis with axoneme assembly

Abstract: Transmission of malaria-causing parasites to mosquitoes relies on the production of gametocyte stages and their development into gametes. These stages display various microtubule cytoskeletons and the architecture of the corresponding microtubule organisation centres (MTOC) remains elusive. Combining ultrastructure expansion microscopy (U-ExM) with bulk proteome labelling, we first reconstructed in 3D the subpellicular microtubule network which confers cell rigidity to Plasmodium falciparum gametocytes. Upon a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
90
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(101 citation statements)
references
References 68 publications
11
90
0
Order By: Relevance
“…Whereas kinesin-8B is part of the axoneme assembly, SAS4 is limited to the BB. This is consistent with previous results showing SAS4 in cytoplasmic compartment associated with the dense BB ( Rashpa & Brochet, 2022 ). We show that SAS4 duplication is synchronized with the accumulation of NDC80 and spindle formation during successive rounds of genome replication during mitosis.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Whereas kinesin-8B is part of the axoneme assembly, SAS4 is limited to the BB. This is consistent with previous results showing SAS4 in cytoplasmic compartment associated with the dense BB ( Rashpa & Brochet, 2022 ). We show that SAS4 duplication is synchronized with the accumulation of NDC80 and spindle formation during successive rounds of genome replication during mitosis.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast to Plasmodium SAS6 that was shown to be important for male gamete formation ( Marques et al, 2015 ), we found that SAS4 is not essential for exflagellation as there was no significant change in flagellated gamete formation. Our findings are corroborated with a recent study showing a non-essential role of SAS4 in parasite transmission, although it described a significant decrease in male gamete formation ( Rashpa & Brochet, 2022 ). At other stages of parasite development, including zygote formation, ookinete and sporozoite development, and parasite transmission and infectivity, no significant differences from the WT-GFP parasite were observed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…2-4). Although recent expansion microscopy data hints at a presence of ring-like structures at gametocyte extremities (Rashpa and Brochet, 2022), there was no evidence of an APR-like structure that could act as a MTOC at gametocyte poles. SPMTs originated at apparently uncoordinated positions and there was no discernible pattern in the distribution of SPMTs along the IMC with respect to the number of protofilaments or secondary tubules.…”
Section: Resultsmentioning
confidence: 89%
“…Recently, expansion microscopy has provided overviews of the SPMT scaffold in some Plasmodium species and forms (Bertiaux et al, 2021; Rashpa and Brochet, 2022) and results from the first purification of tubulin from asexual blood forms were published (Hirst et al, 2022). Even with these advances, our understanding of P. falciparum’s microtubules remains incomplete, particularly in less-studied forms such as the mosquito forms and “pre-sexual” gametocytes.…”
Section: Introductionmentioning
confidence: 99%